How is the practicality of technopreneurship Scientific learning model design in vocational higher education? - Hidayat, Hendra; Herawati, Susi; ., Khairul; Tamin, Boy Yendra; Syahmaidi, Eril (International Journal of Scientific Research and Management (IJSRM), 2018)
This research is aimed to produce a design of learning model in the form of a practical technopreneurship scientific learning model for learning in higher education of vocational education and training. Type of the research is research and development. It was limited to, identify that technopreneurship scientific learning model is practical, and then the product was tested with users; lecturers and students. The questionnaire for assessing the practicality consisted of level of practicality sheet for the users. This instrument was made by using linkert measuring scale. The practicality sheet covered lecturer and students perception towards technopreneurship scientific learning model. It can be practical if it meets the criteria of aspect which is tested to the lecturer to identify attractiveness aspect, aspects of the development process, aspect of user practicality, aspect of functionality and usability, and the aspect of reliability. The result of the research shows that technopreneurship scientific learning model is practical from the lecturer’s view. Besides, from the students’ view, by identifying the students’ interest, the process of its use, improving students` activeness in learning process, the product is also practical. These research findings prove that technopreneurship scientific learning model is practical and be able to be used in higher education, especially in practice courses which expect the students to produce a good product in the form of prototype, blueprint, and concept. This technopreneurship scientific learning model can be developed and used in different courses based on the learning needs.